Cauchy's functional equation and Gaussian measures. Issue 3 (8th October 2019) - Stroock, Daniel W.
Abstract: This article summarizes several examples of the way in which Gaussian measures can be used to obtain results about solutions to Cauchy's functional equation in both finite and infinite dimensions.